Formation and hydration of eco-friendly cement using industrial wastes as raw materials - K. Baltakys (Nature Portfolio, 2021)
Abstract In this work, the optimal conditions of the synthesis of eco-friendly cement by using industrial wastes as well as the peculiarities of its early stage hydration were investigated. The eco-friendly cement was synthesized within the 1000–1250 °C temperature range when the targeted composition was 60% of belite, 20% of ye’elimite, and 20% of brownmillerite. It was determined that the optimal sintering temperature for eco-friendly cement is 1100 °C because the primary compounds were fully reacted, and hydraulic active compounds were dominant in the products. Microcalorimetry analysis was performed for the investigation of early stage hydration. The best results of hydration were obtained with the eco-friendly cement which was produced by using mixtures with silica gel waste: three exothermic reactions were observed in the heat evolution curve, while the cumulative heat was equal to 264 J/g after 72 h. Additionally, the sequence of compounds formation during the first day of hydration was analyzed. It was determined that the composition of the initial mixture impacts the hydration rate of synthetic eco-friendly cement; however, it did not affect the mineralogical composition of the hydration products. These results were confirmed by XRD, STA, and SEM analysis.